Disseminated Cutaneous Leishmaniasis in Colombia: Report of 27 Cases - Iván D. Vélez; Alejandra Jiménez; Daniel Vásquez; Sara M. Robledo (Karger Publishers, 2015)
Disseminated leishmaniasis (DL) is a poorly described disease that is frequently misdiagnosed as other clinical manifestations of cutaneous leishmaniasis (CL) such as diffuse CL or post-kala-azar dermal leishmaniasis. Twenty-seven cases of DL diagnosed between 1997 and 2015 are described. A higher prevalence was observed in men (mean age 32 years). The number of lesions per patient ranged from 12 to 294, distributed mainly in the upper extremities, face and trunk. The lesions were mostly plaques or nodules. Seven patients had nasal mucous damage, 74% of the patients were of mixed race, 92% lived in northwestern Colombia, and Leishmania (Viannia) panamensis was identified as the causative agent in 58% of cases. Eighteen patients recovered with pentavalent antimonial. The importance of distinguishing DL from those other clinical presentations is based on the fact that disseminated, diffuse and post-kala-azar CL are very different in etiology, clinical manifestations and response to treatment and prognosis.